Projections : a story of human emotions - Deisseroth, Karl (Random House, 2021)
"Karl Deisseroth has spent his life pursuing truths about the human mind, both as a practicing clinical psychiatrist and as a researcher who created the revolutionary field of optogenetics, which allows us to decipher the brain's inner workings using light. In his first book, Projections, he combines his groundbreaking access to the brain's inner circuitry with a deep empathy for his patients to examine what mental illness can reveal about the mind and the origin of human feelings--how the broken can illuminate the unbroken. An internationally acclaimed professor of bioengineering and psychiatry at Stanford, Deisseroth's true passion is as a clinical psychiatrist, and it is the stories of his patients that form the backbone of Projections. Through these case studies, he tells the larger story of how we can understand the physical and biological origins of human emotion in the brain. As such, he describes vividly how humans experience feelings both in the simple and ancient circuits of our brains and in the poignant moments of suffering in our daily lives. The stories of Deisseroth's patients are rich with humanity and shine an unprecedented light on the self and the ways in which it breaks down. A young woman with an eating disorder reveals how the mind can rebel against the brain's most primitive drives of hunger and thirst; while an older gentleman, smothered into silence by depression and dementia, illuminates how humans evolved to feel joy and its absence; and a lonely Uyghur woman far from home teaches the importance of rich social bonds. An illuminating and essential work, Projections transforms the way we understand the brain as a biological and as an emotional object"--